Meningkatkan Kepercayaan Diri Siswa SMA melalui Pelatihan Public Speaking di Desa Sinar Bhakti - Angga Saputra; Sarah Pratiwi; Lia Rahni Alvia; Noviansyah Noviansyah; Gitta Destalya Adrian Nova; Hasiatul Aini (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
Public speaking training is a strategic effort to enhance students' confidence, particularly high school students in Sinar Bhakti Village, who often face challenges in effectively communicating in public. This community service activity aims to identify the impact of public speaking training on students' confidence and presentation skills. The training method used is a participatory approach, combining theoretical sessions and practical exercises. Activities include presentation simulations, performance evaluations, and interactive discussions. Additionally, the training is designed to introduce effective communication techniques, such as voice modulation, body language, and logical delivery structure. The results show a significant improvement in students' confidence, their ability to structure presentation materials, and their courage to speak in public. Most participants reported feeling more prepared to face the challenges of speaking in front of an audience after completing the training. This program has also successfully increased students' awareness of the importance of communication skills in supporting their academic and non-academic success. With these achievements, the training is expected to serve as a model for schools to sustainably develop students' communication competencies.